Peningkatan Pengetahuan Tentang Pemberian Asi Eksklusif Dan Pendampingan Balita Gizi Buruk Dan Stunting Di Gresik, Jawa Timur - Amalia Rahma; Annisa Nuradhiani (Ghidza Media Jurnal, 2019)
ABSTRACT This study aims to increase knowledge and awareness of the administration of exclusive breastfeeding and provide assistance to severe malnutrition and stunting toddlers with nutrition education and counseling methods. This research method used quasi-experimental study. The study was conducted in two stages, first stage was the collection of basic data and then interventions according to the causes of the problems found. The subject of this study were 45 toddlers, 11 pregnant women and 15 breastfeeding mothers who had infants less than 6 months. The results showed that after conducting education and counseling for three weeks, there was an increase in the knowledge of pregnant and breastfeeding mothers regarding balanced nutrition for infants / toddlers, increasing from 4% to 24% which was categorized as good and 40% to 16% which was categorized as poor. The knowledge about exclusive breastfeeding increased from 0% which was categorized as good to 72.7%. The results of monitoring body weight, height and intake showed increased but only the total intake of energy and fat showed that increased significantly (energy: p = 0.048 and fat: p = 0.005) so it can be concluded that integrated educational and counseling interventions have the potential to overcome nutritional problems for infants / toddlers malnutrition. Keywords: education, counselling, exclusive breastfeeding, stunting, undernutrition ABSTRAK Penelitian ini bertujuan untuk meningkatkan pengetahuan dan kesadaran pemberian ASI eksklusif serta melakukan pendampingan pada balita yang telah mengalami gizi buruk dan stunting dengan metode edukasi dan konseling gizi. Metode penelitian ini adalah kuasi-eksperimental. Penelitian dilakukan dalam dua tahap yaitu pengambilan data dasar kemudian intervensi sesuai dengan penyebab masalah yang ditemukan. Sebanyak 45 balita, 11 ibu hamil dan 15 ibu menyusui yang memiliki bayi kurang dari 6 bulan yang menjadi subjek penelitian. Hasil penelitian menunjukkan setelah melakukan edukasi dan konseling selama tiga minggu terjadi peningkatan pengetahuan bumil dan busui mengenai gizi simbang untu balita mengalami peningkatan dari 4% menjadi 24% yang dikategorikan baik dan 40 % menjadi 16 % yang dikategorikan buruk. Begitu pula dengan pengetahuan tentang ASI eksklusif meningkat dari 0% yang dikategorikan baik menjadi 72,7%. Hasil monitoring berat badan, tinggi badan dan asupan menunjukkan adanya peningkatan namun hanya intake total energi dan lemak yang meningkat signifikan (energi: p=0,048 dan lemak: p=0,005) sehingga dapat disimpulkan intervensi edukasi dan konseling yang terintegrasi berpotensi untuk mengatasi masalah gizi bagi bayi/balita gizi buruk. Kata kunci : status gizi, persen lemak tubuh, pengetahuan, kebugaran jasmani